The interplay between enterprise and entrepreneur in the flood risk management of small- and medium-sized enterprises in Austria. (20th October 2022) - Winkler, Claudia; Thaler, Thomas; Seebauer, Sebastian
ABSTRACT: Small- and medium-sized enterprises (SMEs) are the backbone of most economies across the globe. They are particularly vulnerable to floods because they typically have less structural adaptation measures and less resources and financial access for recovery than large companies. In SMEs, economic and personal interests in risk governance intersect, such as when business crises after flood impacts spill over to personal crises of entrepreneurs. Applying a qualitative research method comprising policy document analysis, interviews and workshops with 11 flood-affected owner-entrepreneurs and 10 local and federal experts, this article analyses SMEs in the manufacturing sector in Austria. SME vulnerability and coping capacity emerge from the close interaction of (1) the governance framework, foremost the public disaster compensation scheme; (2) enterprise-oriented factors, e.g. availability of capital, customer loyalty, labour force flexibility; and (3) entrepreneur-oriented factors, e.g. psychological resilience, social networks, political efficacy. Flood impacts may increase bankruptcy risk when coinciding with economic and personal challenges. SMEs merit special consideration in disaster risk management, therein accounting for the interplay of enterprise- and entrepreneur-oriented factors. Flood risk managers could introduce mentoring by flood-experienced entrepreneurial peers, consolidate informal local business and political networks, train risk competences of entrepreneurs and promote private insurance.